Computed tomographic evaluation of paediatric brain in a teaching hospital - Islam, MN; Rasul, CH; Sarder, AH; Hossain, SA (Bangladesh Medical Journal Khulna, 2012)
During the period of June 09 to June 11, a total 689 children under 15 year, underwent brain computed tomography in the department of Radiology & Imaging, KMCH. Trauma was the commonest chief complaint (38.6 %), followed by headache (27.3%), convulsion (11.5%), focal neurologic deficit (9.1%), fever (3.5%), developmental delay (2.9%), increasing head size (1.5%), and inability to straighten head (0.9%). Traumatic events (contusion, fracture, extra axial hematoma, intra axial hematoma) were commonest CT diagnoses (24.5%). The other diagnoses were generalized cortical atrophy (7.3%), infarction (4.9%), intracranial tumor (3.3 %), congenital lesions (3.3%), infective process (meningitis, abscess, empyema, encephalitis, tuberculoma, TORCH infection)-2.8%, hypoxic ischemic encephalopathy (2.6%), spontaneous intracranial hemorrhage (2.2%), white matter disease (0.6 %). Negative finding (45%) were also a frequent observation. Proper clinical assessment while advising pediatric brain computed tomography will reduce unnecessary CT scan and in some case initial imaging should be MRI. DOI: http://dx.doi.org/10.3329/bmjk.v44i1-2.10467 Bang Med J (Khulna) 2011: 44(1&2) 3-6